Pengaruh pelatihan asuhan gizi dalam meningkatkan kinerja ahli gizi ruang rawat inap di RSUD DR. Soetomo Surabaya - Indrawati Nurlela; Tjahjono Kuntjoro; Toto Castro (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: Nutrition service department is a part of health care components in a hospital. This department is expected to have better image. Training is needed to improve work performance of dietitians in achieving a professional work.Objective: To find out the influence of nutrition training to work performance of dietitians.Method: This study was pre-experimental with before-after design without control group. Subjects consisted of 15 dietitians and 90 inpatients at Dr. Soetomo Hospital, Surabaya. Data were collected through observation and assessment using questionnaires and check-list, and then analyzed using computer software.Results: There were significant influences of nutrition training to dietitians’ knowledge and attitude (p<0.05). The competence was also significantly improved (p<0.05) with the differentiation points at the first, second, and third month (50.42, 56.16, and 54.11 respectively). Nutrition service output was also significantly improved (p<0.05) with the differentiation points at the first, second, and third month (12.86, 12.40, and 11.06 respectively). There were significant differences in patient satisfaction only when they ate vegetables for lunch, vegetables for dinner, and fruits for lunch (p<0.05).Conclusion: Nutrition training improved work performance of dietitians in providing service for inpatients at Dr. Soetomo Hospital, Surabaya.